Applicated pricing strategies in Jordanian medicine scoter and there effects on customer satisfaction (view point of mangers) - Abo_Dalbouh, Mohmud Agel (Archives of Business Research, 2017)
The aims of study to know the " applicated pricing strategies in Jordanian medicine sector and there effects on customer satisfaction " according to the perspective of the market medicine , pricing , satisfaction and its importance , it focus on a problems faced by prices , customer income , quality , performance of medicine sector . The study showed pricing strategies and there obstacles to achieve customer satisfaction and how to choose the suitable strategy for pricing the medicines and for test the relation between price and satisfaction. The medicine sector face obstacles’ as working capital , cost ,patent regulations’ , laws , customer satisfaction , a suitable strategy and policies to achieve medicine sector objectives ,there are three dimensions’ for independent factors(skimming strategy ,penetration strategy, expected value strategy )and customer satisfaction . The study population is consist of all companies in medicine sector (106) company in survey and analytical study , view point of managers ,concluded that rapid skimming pricing strategy depend on the importance of medicine product but low skimming pricing strategy depend on promotion effort , rapid penetration pricing strategy depend on low price as an entrance for the medicine market. The study showed that :The prices were very high , the market share is low , the customer satisfaction is low the sector, improvement is costly . The study recommended the Jordanian medicine sector must be combining to meet low customer satisfaction by focus on quality , low prices , increase market share , improvement the sector , decrease the cost , reinforce t the competition abilities’